CHEMICAL TRANSFORMATIONS OF PYRIDOXAL AND PYRIDOXAL 5’-PHOSPHATE PRODUCTS WITH L-CYSTEINE, L-SERINE AND L-METHIONINE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The mechanisms of condensation of l-cysteine, l-methionine, and l-serine withpyridoxal and pyridoxal-5-phosphate with l-cysteine were studied by the kinetic method. Unlikemethionine and serine, the condensation of cysteine with pyridoxal and transaldimination withNpyridoxylidene-β-alanine involves intermediate formation of stable product having a thiazolidine ring. Its structure was determined by elemental analysis, UV, and IR spectroscopy, and quantum-chemical calculations. The thiazolidine fragment in the pyridoxal condensation product withl-cysteine is turned through an angle of 90° with respect to the pyridine ring plane due to mutualrepulsion of the negatively charged oxygen atom in the ortho position of the pyridine ring andsulfur and nitrogen atoms in the thiazolidine ring.
Keywords: pyridoxal , pyridoxal-5´-phosphate, cysteine, serine, methionine, kinetics.